2016
DOI: 10.1088/2040-8978/18/3/035402
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear quantum optical properties of graphene

Abstract: We present a semiclassical theory of the linear and nonlinear optical response of graphene. The emphasis is placed on the nonlinear optical response of graphene from the standpoint of the underlying chiral symmetry. The Bloch quasiparticles in the low-energy limit around the degeneracy points are dominantly chiral. It is shown that this chiral behavior in conjunction with scale invariance in graphene around the Dirac points results in the strong nonlinear optical response. Explicit expressions for the linear a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 45 publications
3
48
0
1
Order By: Relevance
“…At higher (infrared, optical) frequencies the inter-band quantum transitions between the electron and hole bands should be taken into account and a quantum theory is needed. Recently, a quantum theory of the third-order nonlinear electrodynamic response of graphene to a uniform external electric field has been proposed in several publications 28,[32][33][34]48 . For example, in Ref.…”
mentioning
confidence: 99%
“…At higher (infrared, optical) frequencies the inter-band quantum transitions between the electron and hole bands should be taken into account and a quantum theory is needed. Recently, a quantum theory of the third-order nonlinear electrodynamic response of graphene to a uniform external electric field has been proposed in several publications 28,[32][33][34]48 . For example, in Ref.…”
mentioning
confidence: 99%
“…[19][20][21][22][23][24] the third-order nonlinear response functions of graphene have been calculated for a single, freely hanging in vacuum (or in air) mono-atomic graphene layer. In reality graphene lies of a dielectric substrate (of thickness d).…”
mentioning
confidence: 99%
“…More general, quantum theories, which take into account both contributions, have been recently proposed in Refs. [19][20][21][22][23][24]. It was shown that, apart from a strong resonance at low (hω ≪ 2E F ) frequencies, the third-order nonlinear conductivity σ αβγδ (ω 1 , ω 2 , ω 3 ) demonstrates a number of resonances at the frequencies corresponding to the one-, two-and three-photon interband absorption.…”
mentioning
confidence: 99%
“…The series of studies on graphene's numerous nonlinear optical processes, as shown in figure 7, can be traced back to contributions by Mikhailov since 2007 [58][59][60][61][62][63] [78][79][80] and more recently by other groups [81][82][83][84][85][86][87][88][89].…”
Section: Nonlinear Optical Properties Of Graphene (A) Theoretical Stumentioning
confidence: 99%
“…Perturbative models are developed to supplement the interband physics, for example the quantum mechanical (QM) Dirac equation model [61,62,64,66,67,89], and also the semiconductor Bloch equations [73,75,76,85]. The QM model replaces v g in equation (3.1) with v g = ψ|∂ H/∂k|ψ , where ψ is the wave function of graphene and H is the Dirac Hamiltonian, which replaces N(p) with N(p) = f (−ε k ) − f (ε k ), the Fermi distribution difference between the conduction and valence bands.…”
Section: Nonlinear Optical Properties Of Graphene (A) Theoretical Stumentioning
confidence: 99%